Differential Susceptibility and Vulnerability of Brain Cells in C57BL/6 Mouse to Mitochondrial Dysfunction Induced by Short-Term Cuprizone Exposure - Luo, Mengyi; Deng, Maomao; Yu, Zijia; Zhang, Yi; Xu, Shuqin; Hu, Shengping; Xu, Haiyun (Frontiers in Neuroanatomy, 2020)
Cuprizone (CPZ) is a chemical chelator toxic to mitochondria of cells. While inducing oligodendrocyte (OL) loss and demyelination, CPZ caused no fatal damage to the other brain cells (neurons, astrocytes, and microglia) in previous studies, suggesting differential susceptibility and vulnerability of brain cells to the CPZ intoxication. To demonstrate this interpretation, C57BL/6 mice were fed rodent chow without or with CPZ (0.2%, w/w) for 7 days. One day later, mitochondrial function of brain cells was assessed by proton magnetic resonance spectroscopy (1H-MRS) and biochemical analysis. Another batch of mice were processed to localize the CPZ-induced damage to mitochondrial DNA, label brain cells, and identify apoptotic cells. Compared to controls, CPZ-exposed mice showed significantly lower levels of N-acetyl-L-aspartate, phosphocreatine, and ATP detected by 1H-MRS, indicating mitochondrial dysfunction in brain cells. Susceptibility analysis showed an order of OLs, microglia, and astrocytes from high to low, in terms of the proportion of 8-OHdG labeled cells in each type of these cells in corpus callosum. Vulnerability analysis showed the highest proportion of caspase-3 positive cells in labeled OLs in cerebral cortex and hippocampus, where neurons showed no caspase-3 labeling, but the highest proportion of 8-OHdG labeling, indicating a lowest vulnerability but highest susceptibility to CPZ-induced mitochondrial dysfunction. Immature OLs, microglia, and astrocytes showed adaptive changes in proliferation and activation in response to CPZ-exposure. These data for the first time demonstrated the CPZ-induced mitochondria dysfunction in brain cells of living mouse and specified the differential susceptibility and vulnerability of brain cells to the CPZ intoxication.